2017
DOI: 10.1038/s41598-017-01807-z
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Sorting of Cells by Viability Based on Differences in Cell Stiffness

Abstract: The enrichment of viable cells is an essential step to obtain effective products for cell therapy. While procedures exist to characterize the viability of cells, most methods to exclude nonviable cells require the use of density gradient centrifugation or antibody-based cell sorting with molecular labels of cell viability. We report a label-free microfluidic technique to separate live and dead cells that exploits differences in cellular stiffness. The device uses a channel with repeated ridges that are diagona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 52 publications
2
65
0
Order By: Relevance
“…8,[11][12][13] Furthermore, dielectrophoresis [6][7][8][9]14 and acoustophoresis 10,11 require active force fields, such as electric and acoustic fields, thereby increasing the system's complexity 15 and compromising its scalability. 16 In addition, for sample flow focusing for efficient cell separation, separation methods based on acoustophoresis, 10,11 deterministic lateral displacement, 12 and cell interaction with periodic ridges 13 require buffer input flow in addition to sample flow. In this study, we demonstrate a novel application of inertial microfluidics for the removal of small (<10 μm) nonviable suspended mammalian cells from a cell culture for standard bioreactors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,[11][12][13] Furthermore, dielectrophoresis [6][7][8][9]14 and acoustophoresis 10,11 require active force fields, such as electric and acoustic fields, thereby increasing the system's complexity 15 and compromising its scalability. 16 In addition, for sample flow focusing for efficient cell separation, separation methods based on acoustophoresis, 10,11 deterministic lateral displacement, 12 and cell interaction with periodic ridges 13 require buffer input flow in addition to sample flow. In this study, we demonstrate a novel application of inertial microfluidics for the removal of small (<10 μm) nonviable suspended mammalian cells from a cell culture for standard bioreactors.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] Test sample cell concentrations are low (up to 2 million mammalian cells per mL). 8,[11][12][13] Furthermore, dielectrophoresis [6][7][8][9]14 and acoustophoresis 10,11 require active force fields, such as electric and acoustic fields, thereby increasing the system's complexity 15 and compromising its scalability. 16 In addition, for sample flow focusing for efficient cell separation, separation methods based on acoustophoresis, 10,11 deterministic lateral displacement, 12 and cell interaction with periodic ridges 13 require buffer input flow in addition to sample flow.…”
Section: Introductionmentioning
confidence: 99%
“…The self-driven microbots and the artificial cilia-based methods, on the other hand, are still in early stages of development. Another relevant factor is that, in general, most adopted approaches (Karimi et al 2013;Bhagat et al 2008Bhagat et al , 2011Di Carlo et al 2007;Kuntaegowdanahalli et al 2009;Wang et al 2013;Islam et al 2017;Huang et al 2004;McGrath et al 2014;Salafi et al 2019;Didar and Tabrizian 2010) Rely on channel shape and structure; the combination of shear forces, inertial effects, and/ or boundary effects, results in one or more lateral equilibrium positions of suspended particles, often depending on particle size, shape, deformability or adhesion (Petersson et al 2004(Petersson et al , 2005Hawkes et al 2004;Collins et al 2015;Melde et al 2016) Suspended (Arai et al 1999;MacDonald et al 2003;Grier and Roichman, 2006) A laser beam with a Gaussian profile carries momentum that is transferred to the particle; this generates a net force on the particle towards the center of the beam. Using holography, multiple of such traps can be created dynamically …”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews of DLD can be found in McGrath et al (2014) and Salafi et al (2019). Examples of approaches in which particle stiffness is utilized to sort the particles can be found in Wang et al (2013) and Islam et al (2017). Finally, adhesion-based sorting has been applied, in particular for cells, in which the target cells selectively bind to specific ligands or other functional coatings applied to the microfluidic channel walls, see, for example, Didar and Tabrizian (2010).…”
Section: Hydrodynamic Methodsmentioning
confidence: 99%
“…The microfluidic approach for studying cellular biomechanics is highly cost effective compared to atomic force microscopy, and has high throughput similar to flow cytometry. Ridged microfluidic channels have been used to separate cells based on stiffness [ 6 ], size [ 7 ], adhesion [ 8 , 9 ], viability [ 10 ], and viscoelasticity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%